Le jaguar, sujet et objet du sacrifice maya - Claude-François Baudez (Journal de la Société des Américanistes)
The jaguar, subject and object in Maya sacrifice. In Maya iconography, the role of the jaguar as a predator associated with all kinds of violence such as war, sacrifice, torture and self-sacrifice, is well-known. Less obvious is its symmetrical and inverse role of victim, on the altar or on the scaffold. Likened to the human warrior, whose fate is to defeat and be defeated, the jaguar is both sacrificer and sacrified.